KUALITAS PERTUMBUHAN PADA MASA BAYI TERHADAP PENCAPAIAN PERKEMBANGAN PADA ANAK PRA SEKOLAH - Firda Fibrila (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2016)
Golden age is important time to caring of children growth and development carefully so abnormality can be detected earlier. Abnormality that often happen in growth and development period is nutrition status problem as indicator of development. The most dangerous growth failure happen in 6-18 month years old. This study purpose is to know growth quality in baby period to development achievement in pre-school children period. This study plan is descriptive and explorative. Sample of this study are mother and 3-5 years old children that have no special needs and registered as student in pertiwi 7 ECD Batanghari east lampung in mei-july 2015 that total 33 students. Data are get use weight and height measurement, interview with mom and child, documentation study and observation. Instrument of this study are checklist, interview guide and KPSP questionnaire. Data is process use univariate. Study result is known proportion quality of baby period growth largely in not good group that is 67,7%, development growth in pre-school children period largely in suitable development group that is 67,7%, respondent proportion with good growth quality with suitable development achievement is 90%. Suggested to teachers to can applied KPSP in ECD so the result can be consideration object to give stimulation to ECD children in study process to increase students motor.